EPID-14. EPIDEMIOLOGY OF ADULT PITUITARY TUMORS IN THE U.S. ACCORDING TO THE 2017 WHO CLASSIFICATION OF ENDOCRINOLOGY TUMOURS. (12th November 2021) - Castellanos, Luz; Gutierrez, Catherine; Smith, Timothy; Iorgulescu, Bryan
Abstract: INTRODUCTION: Among adult intracranial tumors, the pituitary represents a frequent site of origin. We examine their contemporary epidemiology with a particular focus on uncommon pituitary tumor types. METHODS: Adult patients presenting with pituitary or sellar tumors between 2004-2017 were identified from the U.S. National Cancer Database (comprising >70% of newly-diagnosed cancers). Their epidemiology was assessed in the context of the 2017 WHO Classification of Endocrine Tumours. RESULTS: 12.5% of adult intracranial tumors arose in the pituitary region. 113, 352 adults with pituitary tumors were identified. Histopathological diagnosis was obtained in only 59% of cases, in which 93% were pituitary adenomas and 6% were craniopharyngiomas. Among craniopharyngiomas, 71% were adamantinomatous and 29% were papillary, between which there were no differences in age, sex, or tumor size—however, papillary craniopharyngiomas were less common among Black nonHispanic patients (p< 0.001). Among the remaining 1% (n=680) of pituitary tumors, posterior pituitary tumors comprised 21%, chordomas 16%, meningiomas 15%, pituitary carcinomas 11%, GCTs 10%, hematolymphoid 8%, other mesenchymal and stromal 7%, neuronal/paraneuronal 6%, and schwannoma 4%. Meningiomas (84%), mesenchymal/stromal (64%), and neuronal/paraneuronal (64%) tumors displayed a female predominance, whereas GCTs (75%) and pituitary carcinomas (62%) exhibited a male predominance. Age at diagnosis, tumor size, and race/ethnicity varied widely across uncommon tumor types. We further examined the subtypes of uncommon pituitary tumors: for sellar chordomas, 19% were chordoid and none were dedifferentiated; for sellar meningiomas, 94% were grade I; for pituitary GCTs, 79% were pure germinomas; for hematolymphoid, 52% were DLBCL, 11% were plasmacytomas, and 9% were Langerhans cell histiocytosis; for neuronal/paraneuronal, 64% were gangliocytomas; and for mesenchymal tumors, 53% were vascular and 16% were SFTs/HPCs. CONCLUSIONS: Using national registry data, we provide a detailed dissection of the epidemiology of adult pituitary tumors, with a particular focus on examining uncommon pituitary tumor types in the context of WHO2017.